KEEFEKTIFAN MODEL GROUP INVESTIGATION (GI) DALAM PEMBELAJARAN MENULIS PARAGRAF ARGUMENTASI (Eksperimen Kuasi) - Siska Meirita; Mulyanto Widodo (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2017)
This study aimed to describe the effectiveness of the Model Group Investigation (GI) in learning to write a paragraph argument (Experiment Quasi against Civics Department Student Lampung University in the academic year 2013/2014). This study uses a quasi-experimental design. It is concluded that 1) the ability to write a paragraph beginning student argumentation experimental class and control class is no difference with the average value of the experimental class and control class 57.42 and 56.2 and included in the category of less ability level, 2) The ability of the end of the experimental class and control class alike have increased with an average value of 71.8 and 63.6 and included in the category level sufficient capacity, 3) Group Investigation learning model effectively to improve the ability to write a paragraph argumentation, and 4) learning to write paragraphs arguments by using model Group Investigation makes students more active and motivated in learning.Penelitian ini bertujuan untuk mendeskripsikan keefektifan Model Group Investigation (GI) dalam pembelajaran menulis paragraf Argumentasi (Eksperimen Kuasi terhadap Mahasiswa Jurusan PPKN Universitas Lampung Tahun Pelajaran 2013/2014). Penelitian ini menggunakan desain eksperimen kuasi. Kesimpulan penelitian ini adalah 1) Kemampuan awal menulis paragraf argumentasi mahasiswa kelas eksperimen dan kelas kontrol tidak ada perbedaan dengan nilai rata-rata kelas eksperimen dan kelas kontrol 57,42 dan 56,2 dan termasuk dalam kategori tingkat kemampuan kurang, 2) Kemampuan akhir kelas eksperimen dan kelas kontrol sama-sama mengalami peningkatan dengan nilai rata-rata 71,8 dan 63,6 dan termasuk dalam kategori tingkat kemampuan cukup, 3) Model pembelajaran Group Investigation efektif untuk meningkatkan kemampuan menulis paragraf argumentasi, dan 4) pembelajaran menulis paragraf argumentasi dengan menggunakan model pembelajaran Group Investigation membuat siswa lebih aktif dan termotivasi dalam pembelajaran.Kata kunci: group investigation, menulis argumentasi, mahasiswa.